Biochemical and molecular characterization of Vibrio Spp. isolated from hatchery and aquaculture grow-out systems - Julian Ransangan (Universiti Malaysia Sabah, 2007)
Bacterial fauna of sea bass suffering from vibriosis was investigated. Several Vibrio species were isolated and identified using sequencing of partial sequence of 16S rRNA gene. One Vibrio species, V. harveyi strain VHJR7 was tested for its virulence to sea bass, and result showed the bacterium was indeed virulent. LDso derived from challenge test of this pathogen to 100 sea bass juveniles measuring 10-30g body weight was at 1 x 103 CFU/ml. The partial 16S rRNA gene of the pathogen and other Vibrios were deposited into genbank (http://www.ncbLnih.gov) with accession numbers as shown in Table 17 and 18 of this report. Rapid diagnostic method and vaccine for the pathogen is being investigated at the Borneo Marine Institute.